CRITICAL ANALYSIS ON CRYPTOCURRENCY - Sujeetha, R A.P; Haldar, Sarthak; Saha, Bijoy Krishna; Katyayan, Pranjal (International Journal of Computer Sciences and Engineering, 2025)
A cryptocurrency is a digital or virtual currency that uses cryptography for security. A cryptocurrency is difficult to counterfeit because of this security feature. A defining feature of a cryptocurrency, and arguably its most endearing allure, is its organic nature; it is not issued by any central authority, rendering it theoretically immune to government interference or manipulation. The anonymous nature of cryptocurrency transactions makes them well-suited for a host of nefarious activities, such as money laundering and tax evasion